SwiftNINJA steerable microcatheter: a new kid on the block for selective catheterization of vascular and valvular congenital lesions - Haddad, Raymond N.; Adel Hassan, Ahmed; Al Soufi, Mahmoud; Kasem, Mohamed (Frontiers in Cardiovascular Medicine, 2023)
Background SwiftNINJA (Merit Medical Systems, USA) is a novel steerable microcatheter intended for coronary and peripheral vascular interventions. We evaluate and report the first use of SwiftNINJA in pediatric catheterization of congenital heart defects (CHDs). Methods We performed a retrospective clinical data review of children with CHDs in whom SwiftNINJA was used during cardiac catheterization between April 2022 and June 2023. Utility, application, and standard safety were described comprehensively. Results We identified 19 patients (78.9% males) with a median age of 5.3 months (IQR, 2–13.9), and a median weight of 5.3 kg (IQR, 4–7.7). 36.8% of the catheterizations were transarterial and 78.9% were interventional. SwiftNINJA was applied upfront in 3/19 patients to cannulate precisely the right pulmonary artery and eliminate the risk of dislocating a freshly implanted left pulmonary flow restrictor. In 16/19 patients, SwiftNINJA was applied after a median of 5 (IQR, 5–7) failed catheterization attempts using various combinations of catheters, microcatheters, and wires to cannulate challenging vasculature in seven, engage the lumen of stented vessels in five, cross complex aortic valve stenosis in three, and cross an apical ventricular septal defect in one patient with Damus-Kaye-Stansel repair. After the SwiftNINJA application, catheterization was done from the first attempt in 12/16 patients and from the second attempt in 4/16 patients. The median applied tip angulation was 90 degrees (IQR, 85–95). All procedures were completed successfully. No device malfunction or adverse events occurred. Conclusions SwiftNINJA is a valuable addition for selective catheterization of challenging vasculatures or valvular anatomies in children with CHDs.